Enhancement of punching shear behavior of reinforced concrete flat slabs using GFRP grating - Ahmed Mahmoud; Haitham Mostafa; Tarek Mostafa; Ahmed Khater (Fracture and Structural Integrity)
The literature review showed insufficient relevant research on the application of Glass-Fiber-Reinforced-Polymers (GFRP) gratings in the structural elements, while GFRP bars, laminate, sheets, and strips, have been extensively explored. This research aims to present a proposal for a new reinforcing system using GFRP gratings to improve the punching shear resistance of RC flat slabs. Results of seven specimens tested experimentally under vertical static loading are displayed, taking into account the influence of the gratings variables. Test results revealed an improvement in the ultimate load ranging between 9.03% and 27.67% for the specimens strengthened by the proposed GFRP grating system. A Nonlinear Finite Element Analysis (NLFEA) was carried out using the ANSYS program with correlational evaluation using load-deflection response and cracking pattern, which resulted in a good convergence of numerical simulations and experimental performance results ranging from 1.0% to 8.0%. Key parameters, namely the concrete compressive strength, steel reinforcement yield strength, main steel reinforcement ratio, secondary steel reinforcement ratio, column dimensions, slab thickness, concrete cover, and GFRP gratings characteristics, were investigated through a parametric study adopting NLFEA by the ANSYS program, where the output results were compared to the recent code provisions.